2014
DOI: 10.3390/ijms150711473
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Alterations during the Obese-Aging Process in Female and Male Monosodium Glutamate (MSG)-Treated Mice

Abstract: Obesity, from children to the elderly, has increased in the world at an alarming rate over the past three decades, implying long-term detrimental consequences for individual’s health. Obesity and aging are known to be risk factors for metabolic disorder development, insulin resistance and inflammation, but their relationship is not fully understood. Prevention and appropriate therapies for metabolic disorders and physical disabilities in older adults have become a major public health challenge. Hence, the aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 74 publications
3
35
0
2
Order By: Relevance
“…Earlier studies, which have also been confirmed this result on more recent reports on the adverse effects of MSG to increase levels of pro-inflammatory cytokines [33,36]. The anti-inflammatory cytokines are series of immunoregulatory molecules that control the pro-inflammatory cytokine response [37].…”
Section: Discussionsupporting
confidence: 67%
“…Earlier studies, which have also been confirmed this result on more recent reports on the adverse effects of MSG to increase levels of pro-inflammatory cytokines [33,36]. The anti-inflammatory cytokines are series of immunoregulatory molecules that control the pro-inflammatory cytokine response [37].…”
Section: Discussionsupporting
confidence: 67%
“…Our results showed that during the first 16 months, MSG-mice presented metabolic alterations like higher weight gain, higher Lee index, glucose intolerance, insulin resistance and other biochemical parameters like higher cholesterol and triglycerides levels and IL-6, TNF-α, but lower adiponectin (Hernández-Bautista et al 2014). At tissue level, heart, lung, liver and kidney showed progressive lipoperoxidation and protein carbonylation (manuscript in preparation), however all metabolic and oxidative damages did not show significant differences when compared with control mice after 16 months, and MSG-mice even showed higher adiponectin levels with age.…”
Section: Nrf2: Multiple Inductors and Effectsmentioning
confidence: 78%
“…Chronically elevated levels of pro-inflammatory markers, such as interleukin 6 (IL-6) or tumor necrosis factor-α (TNF-α), are key features of ageing since low-grade inflammatory activity in the elderly is common (Starr et al 2009;Bruunsgaard et al 2001). This pro-inflammatory environment has been defined as Binflammaging.^TNF-α and IL-6 have become frailty markers of ageing in humans (Hernandez-Bautista et al 2014); however, the mechanisms that cause and preserve high levels of these markers in ageing are poorly understood.…”
Section: Inflammation and Ageing Inflammagingmentioning
confidence: 99%
“…Lower adiponectin concentrations in obese animals were associated with chronic inflammation, increased TNF-α, and altered glucose and insulin homeostasis (Hernandez-Bautista et al 2014). Plasma adiponectin levels, examined in humans, were not only decreased in obese and diabetic subjects but were also inversely associated with measures of insulin resistance (Gulcelik et al 2013).…”
Section: Adiponectinmentioning
confidence: 99%